Pengaruh Celebirty Endorser, Word of Mouth dan Citra Merek Terhadap Keputusan Pembelian dengan Lokasi Sebagai Variabel Moderasi (Studi Empiris pada Ayam Geprek Bensu di Kota Depok) - Ferdianto, Mario; Mutmainah, Isbandriyati; Yulia, Iis Anisa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine respondents' perceptions regarding Celebrity Endorsers, Word Of Mouth, brand image, purchasing decisions and location and to test the influence of Celebrity Endorser, Word Of Mouth and Brand Image on Purchasing Decisions with Location as a Moderating Variable. The sample used in this research was all Geprek Bensu Chicken consumers in Depok City using 152 respondents. Data was collected using the Non-Probability Sampling method, namely Saturated Sampling (census) and hypothesis testing using multiple linear regression methods and Moderated Regression Analysis (MRA). The results of this research show that Celebrity Endorsers, Word Of Mouth and brand image partially have a positive and significant effect on purchasing decisions. The test results with MRA show that the location variable is able to moderate the influence of Celebrity Endorsers, Word Of Mouth and brand image on purchasing decisions for Ayam Geprek Bensu. The results of the F test show that Celebrity Endorsers, Word Of Mouth and brand image simultaneously have a positive and significant influence on purchasing decisions for Ayam Geprek Bensu